2019
DOI: 10.3390/agriculture9010008
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Response to Salinity in Salt-Tolerant and Salt-Susceptible Cultivars of Date Palm

Abstract: The salinity tolerance mechanism in date palm through antioxidation has not been completely deciphered to date. Therefore, this study aimed to investigate the role of various antioxidants in salinity tolerance. Two date palm cultivars, contrasting in salinity tolerance, were used as model plants in a comparative study designed to detect changes in growth, Na+ and K+ uptake, reactive oxygen species (ROS), and antioxidant accumulations, when plants were exposed to salt stress. The results showed that salinity tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 86 publications
12
48
0
Order By: Relevance
“…Despite both the leaf OP and root OP was decreased in Umsila and Zabad under salinity, these parameters including LWP were less affected in Umsila, suggesting that this cultivar displayed a higher ability to extract water under saline conditions than salt-sensitive Zabad. is feature can be contributed to the capacity of this tolerant cultivar to lower the osmotic potential (osmotic adjustment) under salinity, likely through the production of sugars as shown in International Journal of Agronomy this report and also other osmolytes such as proline as previously shown [11]. It was previously shown that despite the low water potentials in Atriplex L. under salt stress, it could maintain cell turgor pressure and a favorable water absorption gradient because of the ability of this species to adjust osmotically [78][79][80].…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Despite both the leaf OP and root OP was decreased in Umsila and Zabad under salinity, these parameters including LWP were less affected in Umsila, suggesting that this cultivar displayed a higher ability to extract water under saline conditions than salt-sensitive Zabad. is feature can be contributed to the capacity of this tolerant cultivar to lower the osmotic potential (osmotic adjustment) under salinity, likely through the production of sugars as shown in International Journal of Agronomy this report and also other osmolytes such as proline as previously shown [11]. It was previously shown that despite the low water potentials in Atriplex L. under salt stress, it could maintain cell turgor pressure and a favorable water absorption gradient because of the ability of this species to adjust osmotically [78][79][80].…”
supporting
confidence: 63%
“…Determination of salt tolerance mechanism in the date palm requires global omics analysis and rigorous physiological studies [2]. Despite the fact that the association between transcriptomics [7][8][9], metabolomics [10], and biochemical analyses [11][12][13] with salinity tolerance was investigated in the date palm, the importance of physiological parameters including water relations has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruits of the date palm are rich in essential nutrients such as sugars, proteins, fibers, minerals, antioxidants, and vitamins (Vayalil, 2012;Kamal-Eldin and Ghnimi, 2018). To date, several studies have analyzed date palm responses to salinity stress (Sperling et al, 2014;Yaish and Kumar, 2015;Meddich et al, 2018;Ait-El-Mokhtar et al, 2019;Al Kharusi et al, 2019) but few have addressed the effects of AMF inoculation in alleviating salt stress in date palms (Meddich et al, 2018;Ait-El-Mokhtar et al, 2019). Furthermore, no study has yet tested the role of the combined application of AMF and compost in the salt tolerance of date palms and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results obtained by Bolat et al [26] underlined the important role of some antioxidant enzymes like superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), and compounds in protecting cellular mechanisms during water stress conditions. The increase of SOD, CAT and APX, activity and accumulation increase of non-enzymatic antioxidant reagents such as glutathione, phenolic compounds, flavonoids, and proline could represent a key mechanism for salinity tolerance in plant [27].…”
Section: Introductionmentioning
confidence: 99%